A Role for Neutrophils in Viral Respiratory Disease - Camp, Jeremy V.; Jonsson, Colleen B. (Frontiers in Immunology, 2017)
Neutrophils are immune cells that are well-known to be present during many types of lung diseases associated with acute respiratory distress syndrome (ARDS), and may contribute to acute lung injury. Neutrophils are poorly studied with respect to viral infection, and specifically to respiratory viral disease. Influenza A virus (IAV) infection is the cause of a respiratory disease that poses a significant global public health concern. Influenza disease presents as a relatively mild and self-limiting although highly pathogenic forms exist. Neutrophils increase in the respiratory tract during infection with mild seasonal IAV, moderate and severe epidemic IAV infection, and emerging highly pathogenic avian influenza (HPAI). During severe influenza pneumonia (SIP) and HPAI infection, the number of neutrophils in the LRT is correlated with disease severity. Thus, comparative analyses of the relationship between IAV infection and neutrophils provide insights into the relative contribution of host and viral factors that contribute to disease severity. Herein, we review the contribution of neutrophils to IAV disease pathogenesis and to other respiratory virus infections.